ANALYSIS OF CREDIT RISK LEVELS AND MANAGEMENT AMONG POULTRY FARMERS IN IMO STATE, NIGERIA - J.N, Ugwu; J.N, Ugwu; I.J, Uhuegbulem; I.I, Ukoha; A, Tim-Ashama; D.O, Ohajianya; M.O, Okwara; N.F, Dike (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2016)
The study seeks to analyse credit risks levels and management among poultry farmers in Imo State, Nigeria. The study used structured questionnaire to collect data from randomly selected 70 poultry farmers and 12 banks which was purposively selected in the state. Analysis of data was carried out using descriptive statistics such as mean, frequency distribution and percentages. The result of the study revealed that majority of the poultry farmers (75.7%) were males, and were in there active years of age with mean age of 4338 years. 82.9% were married, with a mean years of 8.4 spent in secondary education, and on the average had 11.7 years experience in farming. The mean household size was 6 persons per household with a mean farm income of N303,350 while 65.7% were members of a social organization. Credit default and delayed repayment were some of the major credit risks levels identified in the study area while Majority (86.6% and 82.9) of poultry farmers adopts production and marketing strategies respectively as some of the credit risk management techniques. The study recommends amongst others that proper education of the farmers is necessary for the farmers to learn to use credit for productivity and development as well as the best practices on credit risks management techniques in order to enhance timely repayment and create bright conditions for future credit advances.